The Analgesic and Anti-inflammatory Properties of Caffeine Co-administration with Nefopam in Mice - Ibrahim, Manar ghassan; NA Alabbas, Nibras (The Iraqi Journal of Veterinary Medicine, 2024)
This study aimed to evaluate the analgesic properties of nefopam and the adjuvant effects of caffeine. It also investigated the anti-inflammatory effect of co-administering nefopam and caffeine on Prostaglandin E2 level (PGE2). The study involved 56 female albino mice (Mus musculus), divided into seven groups, eight mice per each group. Group A which served as the control group received distilled water; Group B received 30 mg/kg BW of nefopam orally; Group C received 28.5 mg/BW of nefopam and 5 mg/BW of caffeine orally; Group D received 27 mg/BW of nefopam and 10 mg/BW of caffeine orally; Group E received 25.5 mg/BW of nefopam and 15 mg/BW of caffeine orally; Group F received 24 mg/BW of nefopam and 20 mg/BW of caffeine orally; Group G received 22.5 mg/BW of nefopam and 25 mg/BW of caffeine orally. The nociceptive response was assessed using the formalin test, showing a significant (P<0.05) reduction in pain response (accumulative time of flinching and licking) was the first phase (0-5 minutes) in Group E as well as, a significant (P<0.05) decrease in nociceptive response in flinching and licking in second phase (20-60 minutes) was observed in Group D. However, the Prostaglandin level was significantly (P<0.05) lower in Group C. The study concluded that adding low dosages of caffeine to analgesics can boost pain relief in smaller quantities. Caffeine co-administration with nefopam may exert